A silicon carbide-boron nitride gradient composite ceramic and a preparation method and application thereof

CN118930273BActive Publication Date: 2026-10-23DONGHUA UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411085881.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2026-10-23
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

虽然添加烧结助剂会增强氮化硼陶瓷的强度,但是烧结助剂会残留在氮化硼陶瓷中成为杂质,且一般烧结助剂熔点较低,添加之后会严重减弱氮化硼陶瓷的高温性能,增加烧结压力可以起到增加氮化硼陶瓷相对密度的作用,但过大的烧结压力又会增大工艺实现的难度

Benefits of technology

[0028]本发明的一种碳化硅-氮化硼梯度复合陶瓷及其制备方法,该方法通过引入碳化硅第二相复合并进行梯度陶瓷的设计,在无需添加烧结助剂及施加很大烧结压力的情况下,可以实现氮化硼陶瓷复合材料简单便捷的制备,同时可有效提高其力学性能并保障氮化硼陶瓷材料的高温性能,从而满足侧封板复杂使用环境的要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930273B_ABST
    Figure CN118930273B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of silicon carbide-boron nitride gradient composite ceramics and its preparation method and application, the present application is introduced by silicon carbide second phase composite and carries out gradient ceramic design, without adding sintering aid and under the condition of applying great sintering pressure, it can realize the simple and convenient preparation of boron nitride ceramic composite material, simultaneously can effectively improve its mechanical properties and guarantee the high temperature performance of boron nitride ceramic material, to meet the requirement of complex use environment such as side sealing plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional structural materials, and specifically relates to a silicon carbide-boron nitride gradient composite ceramic, its preparation method, and its application. Background Technology

[0002] Thin strip continuous casting technology is a novel process for producing thin strip steel, which directly obtains steel strips from molten steel at high temperatures. By eliminating the hot rolling and other related processes in traditional continuous casting, twin-roll thin strip continuous casting requires less space, has a simpler process flow, significantly improves production efficiency, and requires less equipment investment and has lower operating costs, making it one of the world's most advanced steelmaking technologies. Side sealing plates play a crucial role in the twin-roll thin strip continuous casting process, constraining the molten metal, promoting strip formation, and ensuring the quality of the strip edges. They require materials with excellent thermal shock resistance, resistance to molten steel erosion, high-temperature volume stability, non-wetting properties with molten steel, and suitable wear resistance.

[0003] Hexagonal boron nitride (BN) is considered an excellent candidate material for thin-strip continuous casting side sealing plates due to its excellent high-temperature self-lubricating properties, good high-temperature resistance, high thermal conductivity, low coefficient of thermal expansion, excellent insulation, and ease of processing. However, despite these superior properties, the extremely strong covalent bonds between the boron and nitrogen atoms within BN make solid-phase diffusion difficult, resulting in a high melting point. Furthermore, its lamellar structure makes it extremely difficult to sinter boron nitride ceramics into a dense structure, significantly limiting its applications. Previous studies have often used the addition of sintering aids or the increase of sintering pressure to promote and improve the densification of boron nitride ceramics. For example, Zhai Fengrui et al. (Zhai Fengrui, Shan Ke, Lu Min, et al. Sintering and structure and properties of hexagonal boron nitride ceramics. Journal of the Chinese Ceramic Society, 2018, 46(6):807-812) prepared h-BN ceramics by SPS sintering under the condition of adding B2O3 as a sintering aid. The results showed that the h-BN ceramics prepared by SPS had finer grains, higher density, and a maximum flexural strength of 120 MPa. Baofo Qiu et al. (Qiu BF, Duan XM, Zhang Z, et al. Microstructural evolution and mechanical properties of h-BN compositeceramics with Y2O3-AlN addition by liquid-phase sintering. Rare (Merals, 2020, 39(5):555-561.) Using Y2O3-AlN as a sintering aid, h-BN ceramics were prepared at 1800℃ by hot pressing. The maximum relative density and flexural strength (161 MPa) were obtained when the Y2O3-AlN addition amount was 40%. Although adding sintering aids can enhance the strength of boron nitride ceramics, the sintering aids will remain in the boron nitride ceramics as impurities. In addition, sintering aids generally have low melting points, and their addition will seriously weaken the high-temperature performance of boron nitride ceramics. Increasing the sintering pressure can increase the relative density of boron nitride ceramics, but excessive sintering pressure will increase the difficulty of process implementation.

[0004] Because the side sealing plate needs to be in direct contact with molten steel, the temperature of the contact surface is extremely high, reaching about 1650℃. There is a temperature difference of over 100℃ between the side sealing plate and the interior. Once the internal stress generated by the temperature gradient exceeds the material strength, the side sealing plate will break, leading to its failure.

[0005] Therefore, how to design and provide a high-performance boron nitride ceramic material and its preparation method to achieve simple and convenient preparation of the ceramic material and meet the requirements of the complex use environment of the side sealing plate is a key problem that needs to be solved by the scientific and technological personnel in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the technical problem to be solved by this invention is to provide a silicon carbide-boron nitride gradient composite ceramic, its preparation method, and its application.

[0007] The present invention provides a silicon carbide-boron nitride gradient composite ceramic, wherein the silicon carbide content in the silicon carbide-boron nitride gradient composite ceramic is distributed in a gradient.

[0008] The gradient composite ceramic is composed of boron nitride composite ceramics containing different mass fractions of silicon carbide distributed in a layered manner.

[0009] The silicon carbide content in the gradient ceramic varies in a gradient manner from the outer layer to the middle layer, either decreasing or increasing.

[0010] This invention provides a method for preparing silicon carbide-boron nitride gradient composite ceramics, comprising:

[0011] (1) Silicon carbide and boron nitride were mixed according to the ratio to prepare composite powders of silicon carbide and boron nitride with different ratios;

[0012] (2) Lay out layers according to the gradient distribution of silicon carbide content and pre-press to obtain ceramic green body;

[0013] (3) The pre-pressed blank is sintered under an inert atmosphere to obtain silicon carbide-boron nitride gradient composite ceramic.

[0014] Preferably, in step (1), the boron nitride is composed of hexagonal boron nitride and cubic boron nitride, with hexagonal boron nitride accounting for 70-85% of the total boron nitride mass and cubic boron nitride accounting for 15-30%.

[0015] Preferably, in step (1), the average particle size of silicon carbide powder is 100 nm or less; the average particle size of hexagonal boron nitride is 1 μm or less; and the particle size of cubic boron nitride is 500 nm or less.

[0016] The mixing method in step (1) is three-dimensional mixing, etc.

[0017] In step (2), a steel mold is used to spread powders of different proportions layer by layer and pre-press them to obtain ceramic blanks.

[0018] Preferably, in step (2), the gradient distribution of silicon carbide content is such that the silicon carbide content first increases gradually to the intermediate layer and then decreases gradually, or first decreases gradually to the intermediate layer and then increases gradually.

[0019] Preferably, the pre-compression pressure in step (2) is 50 to 250 MPa.

[0020] Preferably, the inert atmosphere in step (3) is at least one of argon and nitrogen; the pressure sintering is hot pressing sintering or discharge plasma sintering, wherein the sintering temperature is 1800-2000℃, the sintering pressure is 20-60MPa, and the holding time is 5-100min.

[0021] Preferably, in step (3), the silicon carbide-boron nitride gradient composite ceramic has m layers; wherein the composition and thickness of the axisymmetric layers are the same with the middle layer as the axis of symmetry; wherein m≥3.

[0022] Preferably, the silicon carbide-boron nitride gradient composite ceramic consists of 5 layers, wherein the first and fifth layers have the same powder composition, the second and fourth layers have the same powder composition, and the third layer is an intermediate layer.

[0023] Preferably, m = 5; wherein the silicon carbide content in the first and fifth composite ceramic layers is 0–25 wt.%, the silicon carbide content in the second and fourth composite ceramic layers is 0–25 wt.%, and the silicon carbide content in the third composite ceramic layer is 0–25 wt.%.

[0024] Preferably, m = 5; wherein the thickness of the first and fifth layers accounts for 10-50% of the total thickness, the thickness of the second and fourth layers accounts for 10-50% of the total thickness, and the thickness of the third layer accounts for 10-50% of the total thickness.

[0025] Gradient distribution of silicon carbide content in silicon carbide-boron nitride gradient composite ceramics; wherein the silicon carbide content first increases in gradient to the intermediate layer and then decreases in gradient, or first decreases in gradient to the intermediate layer and then increases in gradient.

[0026] The component distribution index in the silicon carbide-boron nitride gradient composite ceramic is 0.8 to 1.2.

[0027] This invention provides an application of the silicon carbide-boron nitride gradient composite ceramic in the field of thin strip continuous casting side sealing plate materials.

[0028] This invention discloses a silicon carbide-boron nitride gradient composite ceramic and its preparation method. This method introduces a second phase of silicon carbide and designs a gradient ceramic, enabling the simple and convenient preparation of boron nitride ceramic composite materials without the need to add sintering aids or apply high sintering pressure. At the same time, it can effectively improve its mechanical properties and ensure the high-temperature performance of boron nitride ceramic materials, thereby meeting the requirements of complex use environments for side sealing plates.

[0029] Beneficial effects

[0030] This invention introduces silicon carbide as a second phase and employs a gradient design to prepare silicon carbide-boron nitride gradient composite ceramics. This method eliminates the need for sintering aids and high sintering pressure, enabling simple and convenient preparation. The composite ceramics exhibit higher Young's modulus and flexural strength, as well as a lower coefficient of thermal expansion. Because no sintering aids are used in the preparation process, the high-temperature performance of the boron nitride ceramics is guaranteed. Furthermore, compared to traditional single-component boron nitride ceramics, the properties of the prepared gradient composite ceramics can be adjusted according to different application environments, thus meeting the needs of more application scenarios and promoting the application and development of boron nitride materials. Attached Figure Description

[0031] Figure 1 This is a cross-sectional view of the sample with n=1.0 in Embodiment 1 of the present invention;

[0032] Figure 2 These are the flexural and compressive strengths of each sample in Example 1 of this invention;

[0033] Figure 3 These are the Young's moduli of each sample in Example 1 of this invention;

[0034] Figure 4 This refers to the change in the coefficient of thermal expansion of each sample with temperature in Example 1 of the present invention;

[0035] Figure 5 This is a cross-sectional view of the sample in Embodiment 2 of the present invention;

[0036] Figure 6 This is a scanning electron microscope image of the sample in Example 2 of the present invention. Detailed Implementation

[0037] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0038] Related tests:

[0039] The flexural and compressive strength of the samples were measured using a universal testing machine. For the three-point flexural strength measurement, the sample was cut into a four-sided strip with a cross-sectional side length of 3×3 mm and a length of not less than 26 mm. The pressure loading rate was 0.05 mm / min, and the maximum load at which the sample broke was recorded. The experiment was repeated at least 6 times for each sample.

[0040] To measure the compressive strength, the sample was cut into a cubic prism with a side length of 3±0.1 mm, and the load was applied at a rate of 0.1 mm / min. The critical load that the test sample could withstand was recorded.

[0041] The hardness of the samples was measured using a Vickers hardness tester. The samples were tested after being polished. Five data points were measured for each sample and the average value was calculated.

[0042] The thermal diffusivity of h-BN in the direction parallel to the sintering pressure was measured using a laser thermal conductivity meter. The sample was a circular disc with a diameter of 10 mm and a thickness of 2 mm. After the surface was polished, washed, dried, and coated with carbon powder, it was placed in the laser thermal conductivity meter to test the thermal diffusivity. Four temperature points were selected: 30℃, 200℃, 400℃, and 600℃.

[0043] The coefficient of thermal expansion of the sample was measured using a thermal dilatometer. The sample was cut into a quadrangular prism with a cross-sectional side length of 3×3mm and a length of 17mm. The surface of the sample was polished smooth, with the angle between adjacent faces forming a 90° angle. The sample was then placed in the thermal dilatometer to measure the coefficient of thermal expansion.

[0044] raw material:

[0045]

[0046] Example 1

[0047] The boron nitride powder was weighed according to the following formula: the silicon carbide content in the first and fifth layers was 0 wt.%, the silicon carbide content in the second and fourth layers was 5 wt.%, and the silicon carbide content in the third layer was 10 wt.%. In the above boron nitride powder, hexagonal boron nitride accounted for 70% of the total boron nitride, and cubic boron nitride accounted for 30%. A three-dimensional mixer was used to mix the powder, and according to the thickness ratio in Table 1, the powder was spread evenly in a steel mold from layer 1 to layer 5. The spread powder was pre-pressed at 150 MPa to obtain a green body. A discharge plasma sintering process was used, sintering at 2000℃ and 50 MPa for 5 minutes. A cross-sectional view of the sample with n=1.0 is shown below. Figure 1 As shown.

[0048] like Figure 2 , 3 As shown, gradient design significantly improves the flexural strength and Young's modulus of boron nitride ceramics. With increasing component distribution index n, the flexural strength initially increases and then decreases, reaching its maximum at n=1.0 (190 MPa). The compressive strength at n=1.2 reaches 286.3 MPa, and the Young's modulus varies between 36.6 GPa and 39.62 GPa. Figure 4 The change in the coefficient of thermal expansion can be observed, showing that the gradient design significantly reduces the coefficient of thermal expansion of boron nitride ceramics at low temperatures, with the lowest coefficient of thermal expansion reaching 1.2 × 10⁻⁶ at 200 °C. -6 K -1The coefficient of thermal expansion of the prepared sample is between that of boron nitride ceramics containing 5% silicon carbide and those containing 10% silicon carbide, indicating that gradient design can control the coefficient of thermal expansion of boron nitride ceramics by changing the thickness of the gradient layer.

[0049] Table 1

[0050]

[0051] Example 2

[0052] The boron nitride powder was weighed according to the following formula: the silicon carbide content in the first and fifth layers was 10 wt.%, the silicon carbide content in the second and fourth layers was 5 wt.%, and the silicon carbide content in the third layer was 0 wt.%. In this boron nitride powder, hexagonal boron nitride accounted for 80% of the total boron nitride, and cubic boron nitride accounted for 20%. The powder was mixed using a ball mill, and according to the thickness ratio of n=1.0 in Table 1, the powder was evenly spread in a steel mold from layer 1 to layer 5. The spread powder was pre-pressed under a pressure of 200 MPa to obtain a green body. Hot pressing sintering was performed at 1900℃ and 50 MPa for 50 min. A cross-sectional view of the sample is shown below. Figure 5 As shown, the microstructure of the sample is as follows Figure 6 As shown in the figure, the sample obtained by hot pressing and sintering has large grains, which are hexagonal and have a size of more than ten micrometers.

Claims

1. A method for preparing a silicon carbide-boron nitride gradient composite ceramic, comprising: (1) Silicon carbide and boron nitride were mixed according to the ratio to prepare composite powders of silicon carbide and boron nitride with different ratios; (2) Lay up the silicon carbide content according to the gradient distribution and pre-press it to obtain a ceramic body; wherein the gradient distribution of silicon carbide content is that the silicon carbide content first increases to the middle layer and then decreases, or first decreases to the middle layer and then increases. (3) The silicon carbide-boron nitride gradient composite ceramic was obtained by pressure sintering under an inert atmosphere; The sintering temperature is 1800~2000℃, the sintering pressure is 20~60MPa, and the holding time is 5~100min; The silicon carbide-boron nitride gradient composite ceramic has an axis of symmetry with the intermediate layer as its axis of symmetry, and the composition and thickness of the axisymmetric layers are the same. The silicon carbide-boron nitride gradient composite ceramic consists of 5 layers, wherein the 1st and 5th layers have the same composition, the 2nd and 4th layers have the same composition, and the 3rd layer is the intermediate layer. The silicon carbide content in the 1st and 5th composite ceramics is 0~25wt.%, the silicon carbide content in the 2nd and 4th composite ceramics is 0~25wt.%, and the silicon carbide content in the 3rd composite ceramic is 0~25wt.%.

2. The preparation method according to claim 1, characterized in that, In step (1), boron nitride is composed of hexagonal boron nitride and cubic boron nitride, with hexagonal boron nitride accounting for 70-85% of the total boron nitride mass and cubic boron nitride accounting for 15-30%. In step (1), the average particle size of silicon carbide powder is less than 100 nm; the average particle size of hexagonal boron nitride is less than 1 μm; and the particle size of cubic boron nitride is less than 500 nm.

3. The preparation method according to claim 1, characterized in that, The pre-compression pressure in step (2) is 50~250MPa.

4. The preparation method according to claim 1, characterized in that, In step (3), the inert atmosphere is at least one of argon and nitrogen; the pressure sintering is hot pressing sintering or discharge plasma sintering.

5. The preparation method according to claim 1, characterized in that, The thickness of the first and fifth layers accounts for 10-50% of the total thickness, the thickness of the second and fourth layers accounts for 10-50% of the total thickness, and the thickness of the third layer accounts for 10-50% of the total thickness.

6. A silicon carbide-boron nitride gradient composite ceramic prepared by the method of claim 1, characterized in that, The silicon carbide content in the silicon carbide-boron nitride gradient composite ceramic exhibits a gradient distribution.

7. The application of the silicon carbide-boron nitride gradient composite ceramic of claim 6 in the field of thin strip continuous casting side sealing plate materials.

Citation Information

Patent Citations

  • Composite side sealing plate and preparation method thereof

    CN117600422A